Kebutuhan Pengembangan Media Pembelajaran iSpring Suite Berbasis Android Pada Mata Pelajaran Morfologi Bahasa Arab - Vera Fikrotin; Siti Sulaikho (UIN Sunan Gunung Djati Bandung, 2021)
Learning media is an important component so that the process of teaching and learning activities in class is carried out properly. Learning media as a means or intermediary tool in order to convey messages in the form of learning. This study aims to determine the needs of students in learning media Shorof. Where the effective media is the media according to the needs of students. The researcher uses the R&D method with a 4D Thiagarajan model in this study which consists of defining, planning, developing and disseminating. In collecting data, the researchers conducted observations and gave questionnaires to students' media needs. The average results show that students need learning media that can be accessed at any time to increase enthusiasm for learning in class VIII A with a percentage value of 79.00% (Required) and class VIII B with a percentage value of 83.00% (Required). The results of the percentage value state that students need an Android-based ispring suite learning media on shorof subjects because it can be accessed anytime.